Rare Presentation of Cardiotoxicity Related to 5-Fluorouracil - Mariam Charkviani; Natia Murvelashvili; Francisco Barrera; Alisha Sharma; Randa Sharag Eldin; Nur Un Nisa Nabil (Case Reports in Oncological Medicine)
5-Fluorouracil (5-FU) is a chemotherapeutic agent frequently used for the treatment of solid tumors. In a few cases, 5-FU can be associated with coronary vasospasm, cardiac ischemia, or life-threatening arrhythmias. Recognition of 5-FU cardiotoxicity is clinically important as after the rapid sensation of therapy, cardiotoxicity can be completely reversible, and on the other hand, readministration may lead to serious damage of the heart and even death. A 70-year-old male came to the emergency department (ED) with chest pain which started while receiving an infusion of 5-FU. The patient did not have a personal history or risk factors of coronary artery disease and his electrocardiogram (ECG) before starting chemotherapy was completely normal. In the ED, his ECG had ischemic changes, troponin was elevated, and echocardiogram showed anterior wall hypokinesis. However, emergent coronary angiogram did not reveal any acute coronary occlusion. 5-FU-induced cardiotoxicity was suspected; the patient was admitted to a progressive care unit for close monitoring and infusion of calcium channel blockers was initiated. The patient’s symptoms and ECG findings gradually resolved, and two days later on discharge, patient was chest pain free and ECG was normal. This case supports the vasospastic hypothesis of 5-FU cardiac toxicity, describes its clinical course, and emphasizes the importance of better awareness and early recognition of the rare side effect as it may allow physicians to reduce the risk of life-threatening complications.